The Involvement and Conflict of Authority of Actors Managing the Indonesia-East Malaysia Border Area - Ida Rochmawati; Rusdiono Rusdiono; Arifin Arifin (Universitas Sultan Ageng Tirtayasa, 2022)
The management of Indonesian border areas encounters many complex problems in terms of the regional environment and border management actors. The objective of this study was to explore the involvement of actors and their authority in managing border areas. In this study, the researchers employed a qualitative approach to reveal the involvement of each actor and their authority. Results showed that the border area is a new arena for the Central Government as the main actor in terms of political affairs and public policies. This condition leads to a conflict of authority between actors. The Regional Government plays a role as the second actor acting as a passive object. In reality, management of border areas has not been developed by Central and Regional Governments seriously both in terms of distribution, autonomy, and reinforcement of authority. This makes the issue of the management of border areas complicated, especially to make border areas a connecting point of the state with neighboring countries by emphasizing a comprehensive welfare-oriented development program for each region without compromising the security approach. Based on the results of this study, it is recommended that constructing and building a complete synergy pattern between management actors are crucial starting points in developing border areas.